Analisis Sarana Retorika dalam Novel Jelatik Karya Riki Utomi - Putri, Yola Yolanda; Asnawi, Asnawi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
In the era of increasingly visual and concise digital communication, the ability of literary writers to maintain the power of language through rhetorical means is becoming increasingly important. Rhetoric in literary works not only beautifies speech, but also becomes an effective medium for conveying messages, building character, and shaping reader awareness. This study aims to identify and analyze the use of rhetorical devices in Riki Utomi's novel Jelatik. The research method used is descriptive qualitative with a hermeneutic approach. Data collection techniques are carried out through literature studies and intensive reading of the novel text using reading and note-taking techniques. Interpretive analysis is used to determine the meaning, purpose, and significance of quotations that incorporate figures of speech, imagery, and structural investigations to the novel's overall narrative structure. The study's findings demonstrate how Jelatik often uses a variety of comparative figures of speech, including personification, simile, and metaphor, as well as linking figures of speech, such metonymy and synecdoche, to enhance symbolic value in her book. Furthermore, it has been discovered that repeated figures of speech, such parallelism, anaphora, and repetition, heighten emotional nuances and highlight ideas. Structural investigation is carried out through repetition, parallelism, and anaphora. In terms of imagery, the author utilizes visual, auditory, olfactory, tactile, and movable imagery to bring the reader's sensory experience to life and strengthen the narrative atmosphere. The implications of this study not only add to the treasure trove of stylistic studies in Indonesian literature, but also contribute to literature learning in schools, especially in developing students' appreciation of the power of language and local values in literary works.